2024
DOI: 10.1002/sd.2861
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the nexus between the barriers and drivers for sustainable smart cities in developing countries: The case of Nigeria

Abdulkabir Opeyemi Bello,
Taofeek Tunde Okanlawon,
Ibrahim Yahaya Wuni
et al.

Abstract: Amidst the rapid urbanisation and increasing calls for sustainable development, this study examines the key drivers and barriers influencing sustainable smart city initiatives in Nigeria. By employing a quantitative approach, the research amalgamates insights from diverse professionals, integrating descriptive statistics, exploratory factor analysis, and Spearman rank correlation analysis to illuminate the intricate landscape of sustainable smart city development within the Nigerian context. The findings under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 157 publications
0
0
0
Order By: Relevance
“…Research by Bello et al [40] on Indian cities revealed that the design and implementation of SSCs in developing countries are markedly different. The main barriers identified in the various cities include the following:…”
Section: Discussion and Contributionsmentioning
confidence: 99%
“…Research by Bello et al [40] on Indian cities revealed that the design and implementation of SSCs in developing countries are markedly different. The main barriers identified in the various cities include the following:…”
Section: Discussion and Contributionsmentioning
confidence: 99%